Analysis of expression pattern of proteins associated with AKT/mTOR signaling pathway in kidney cancer development - Ritesh Satardey; Ravi Yadav; Madhusudan Das; Dilip Kumar Pal (Annals of Medical Science and Research)
Introduction: The purpose of this study was to analyze the expression status, reciprocal interplay, and prognostic significance of AKT1 and hypoxia-inducible factor 1 alpha (HIF-1α) in AKT/mechanistic target of the rapamycin pathway and to enable them to be studied as possible therapeutic targets. Materials and Methods: This prospective study included 25 patients with clear cell renal cell carcinoma (ccRCC) operated between December 2019 and January 2022. Tumor and adjacent normal tissue samples were subjected to immunohistochemical analysis, RNA extraction, cDNA synthesis, and quantitative real-time polymerase chain reaction for AKT and HIF-1α. The fold changes were then calculated by ΔΔCt method. Results: The included 25 ccRCC patients had 1.5-fold greater HIF-1 mRNA expression and 0.9-fold higher AKT1 gene expression in the ccRCC tissues compared to the corresponding healthy control. High, moderate, and low expression of HIF-1α was seen in 15, 6, and 1 of 25 samples, respectively. High, moderate, and low expression of p-AKT1 was seen in 18, 2, and 3 of 25 samples, respectively. Conclusion: Our study data predicted higher gene expression as well as protein expression of HIF-1α and AKT. The proteins HIF-1α and AKT are localized in the nucleus of the RCC tumor samples compared to normal. Overexpression of these proteins might play significant roles in tumor development and differentiation as reported by others previously. This study can help clarify the biological role of HIF-1α and AKT in RCC to develop new strategies for this malignancy.